2013
DOI: 10.1016/s0140-6736(13)61570-6
|View full text |Cite
|
Sign up to set email alerts
|

A two-decade comparison of prevalence of dementia in individuals aged 65 years and older from three geographical areas of England: results of the Cognitive Function and Ageing Study I and II

Abstract: SummaryBackgroundThe prevalence of dementia is of interest worldwide. Contemporary estimates are needed to plan for future care provision, but much evidence is decades old. We aimed to investigate whether the prevalence of dementia had changed in the past two decades by repeating the same approach and diagnostic methods as used in the Medical Research Council Cognitive Function and Ageing Study (MRC CFAS) in three of the original study areas in England.Methods Between1989 and 1994, MRC CFAS investigators did b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
735
7
26

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 888 publications
(792 citation statements)
references
References 28 publications
24
735
7
26
Order By: Relevance
“…Two time points are given for CFAS I: the baseline assessment, which is more directly comparable to the CFAS II baseline assessment, and the 10-year follow-up wave in which service use was measured. Consistent with the main findings from CFAS II, 164 the prevalence of dementia reduced slightly between the CFAS I baseline and the CFAS II baseline assessments. Over the same period the prevalence of stroke and VI remained similar.…”
Section: Results From the Cognitive Functioning And Ageing Studies Ansupporting
confidence: 85%
See 1 more Smart Citation
“…Two time points are given for CFAS I: the baseline assessment, which is more directly comparable to the CFAS II baseline assessment, and the 10-year follow-up wave in which service use was measured. Consistent with the main findings from CFAS II, 164 the prevalence of dementia reduced slightly between the CFAS I baseline and the CFAS II baseline assessments. Over the same period the prevalence of stroke and VI remained similar.…”
Section: Results From the Cognitive Functioning And Ageing Studies Ansupporting
confidence: 85%
“…Analysis within CFAS II only showed that unpaid care was used substantially more by those with dementia and a target health condition than by those with the health condition alone. Previous analysis in CFAS has shown that fewer people are moving into care settings, 164 which could, in turn, influence the use of unpaid care. It is well documented that those with dementia and their carers have difficulties with accessing the support that they need day to day.…”
Section: Carer Inclusion and Supportmentioning
confidence: 99%
“…For example, Danish 90-year olds and older born later (1915) reached higher cognitive test scores than approximately same-aged individuals born earlier (1905;Christensen et al, 2013). Similarly, 75-year olds and older in Great Britain in 2008 -2011 had lower prevalence rates of dementia than the parallel cohort in 1989 -1994 (Matthews et al, 2013). However, initial evidence has indicated that these historical improvements do not persist into the last years of life (Hülür et al, 2013).…”
Section: Historical Trends In Cognitive Performance and Well-being Inmentioning
confidence: 99%
“…& Sandrine Andrieu sandrine.andrieu@univ-tlse3.fr despite suggestions of a decrease in their incidence in western countries [2][3][4]. The annual global cost of dementia is estimated at more than US$600 billion [5].…”
Section: Introductionmentioning
confidence: 99%